Strategi Pembelajaran Bahasa Arab dalam Kemahiran Menulis (Al-Imla) Di Pondok Pesantren Al Khairaat Salilama Kecamatan Mananggu Kabupatenn Boalemo Provinsi Gorontalo - Muhammad Shadiq Ladiku; Titin Fatimah (Albariq: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to determine the strategies used and what difficulties students experience in learning Arabic in writing skills (Al-Imla) at the Al-Khairaat Salilama Islamic Boarding School, Mananggu District, Boalemo Regency, Gorontalo Province. The approach used in this study is a qualitative approach, with data collection techniques through interviews, observation, and documentation. The results showed that the strategy for learning Arabic in writing skills (Al-Imla) was applied at the Al-Khairaat Salilama Islamic Boarding School, Mananggu District, Boalemo Regency, Gorontalo Province, had two strategies for implementing Arabic learning, namely the strategy learning in inside and outside the classroom.